PARASITES GENERAL CHARACTERISTICS SIGNIFICANCE FOR HUMANS - RATNESH KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
Moreover, all of them are hermaphrodite, and both asexual reproduction (mostly paratomy) and sexual reproduction are present. Bilateral symmetry, multiciliated epidermis, absence of an accessory centriolus at the ciliary roots, more than one cilia in the terminal cell of the protonephridia, stem cells as differentiation cells, presence of a male porus and male copulatory organ, and dorsoventral and anteroposterior polarity are the classical characteristics that define the phylum Platyhelminthes (Ehlers, 1985; Ax, 1995). Along the primary axis of the body, the pharynx may be found in a variety of positions, depending on whether it is simplex, plicatus, or rosulatus. The oral opening is usually found in the central region of the animal, and the intestine is a blind sac that does not have an anus. The protonephridial system is the route that waste products take out of the body. Hermaphrodites are referred to as turbellarians. The many elements of the male copulatory organ that combine to generate stylets may vary in terms of their intricacy and shape, but they are the reproductive structures that stand out the most.